An evaluation scale for the cultural value of heritage buildings - Hai Huang; Mohd Khairul Azhar Mat Sulaiman; Nor Zalina Harun; Wanting He (PLoS ONE, 2026)
As a repository of human history and a conduit for culture, heritage buildings represent the primary central focus of heritage conservation. However, the lack of a comprehensive framework for evaluating the cultural value of heritage buildings is a significant challenge. Based on a systematic review of the classification of cultural value in cultural heritage over the past two decades, this study employed face-to-face interviews with ten local shop owners, go-along interviews with ten visitors, and a Focus Group Discussion (FGD) with five experts in Longxing Ancient Town, Chongqing, China. The interview transcripts were coded and analyzed with NVivo software, the FGD results were analyzed manually, and the weights of the indicators were assigned using the Analytical Hierarchy Process (AHP). Ultimately, by synthesising the perspectives of various stakeholders, the Cultural Value Evaluation Scale (CVES) for heritage buildings was developed for the first time. This scale, designated as the LHSSA Framework (Local value, Historic value, Sustainability value, Scientific value, Aesthetic value), encompasses five primary indicators and 24 secondary indicators. The scale offers considerable theoretical significance and practical value for the identification of heritage value and the improvement of the heritage value evaluation system.